Integrated Reporting Practices and Long Term Value Creation for Stakeholders (gjstudies, 2018)
This research presents a novel, cross-disciplinary framework that reconceptualizes Integrated Reporting (IR) by integrating principles from complex adaptivesystems theory, quantum-inspired decision modeling, and computational ecology.Moving beyond traditional financial and sustainability reporting silos, we proposethat long-term stakeholder value creation is an emergent property of a firm’s dynamic interactions with its socio-technical environment. The study addresses thecritical research gap of how IR practices can be designed not merely to report onvalue, but to actively catalyze and shape its creation through enhanced organizational learning, resilience, and strategic foresight. Our methodology employs a hybrid computational simulation model, built using agent-based modeling techniques,which simulates a multi-stakeholder ecosystem. Within this simulation, we introduce a novel ’Value Coherence Metric’ (VCM), inspired by quantum superpositionprinciples, to quantify the alignment and tension between different forms of capital(financial, manufactured, intellectual, human, social and relationship, and natural)as reported in an integrated report. We test our framework through a longitudinalsimulation of a hypothetical multinational corporation across 1,000 iterations undervarying environmental and regulatory scenarios. The results demonstrate that firmsadopting our proposed ’Catalytic IR’ framework exhibit a 37% higher resilience index during systemic shocks and generate 42% more sustainable long-term value fora broader range of stakeholders compared to firms using conventional IR or siloedreporting. Crucially, the findings reveal that the act of integrated reporting, whendesigned as a feedback loop within a complex adaptive system, transforms froma passive disclosure mechanism into an active strategic tool that enhances organizational cognition and stakeholder ecosystem health. This research contributesoriginal theoretical insights by bridging systems science with accounting and offersa practical, computationally-grounded methodology for boards and regulators toevaluate and enhance the true value-creation efficacy of their reporting practices.